Pola Penerapan Pembelajaran Berdiferensiasi pada Pelajaran Pendidikan Pancasila Kelas X MAN 2 Kota Bogor (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the role of Pancasila and Citizenship Education (PPKn) teachers in shaping the character of students at MAN 2 Kota Bogor. The research method used is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that Civics teachers have an important role in shaping the character of students through exemplary, habituation, and learning moral and national values. Teachers act as motivators, facilitators, and mentors in instilling Pancasila values such as responsibility, honesty, and discipline. In conclusion, the role of Civics teachers is vital in shaping the character of students with integrity and high nationalism.